Femtosecond laser-assisted arcuate keratotomy for the management of corneal astigmatism in patients undergoing cataract surgery: Comparison with conventional cataract surgery - Ahn, Hyunmin; Jun, Ikhyun; Seo, Kyoung Yul; Kim, Eung Kweon; Kim, Tae-im (Frontiers in Medicine, 2022)
Purpose: To assess the effects of femtosecond laser arcuate keratotomy with femtosecond laser-assisted cataract surgery in the management of corneal astigmatism, compared with conventional phacoemulsification cataract surgery. Design: Retrospective comparative interventional case series. Methods: A total of 2498 eyes of consecutive patients who presented with 3.00 diopters (D) or under of astigmatism were included. The patients were treated with conventional phacoemulsification cataract surgery (conventional group) and femtosecond laser arcuate keratotomy with femtosecond laser-assisted cataract surgery (femtosecond group). Results: Surgically induced astigmatism (SIA) was higher in the femtosecond group than the conventional group (0.215, p<0.001). Difference vector (DV) was lower in the femtosecond group (-0.136, p<0.001). The cut-off value of the overcorrection in the femtosecond group was 0.752 D of target induced astigmatism (TIA). For patients with TIA 0.75 D or under, DV and the value of index of success (TIA into DV) were significantly higher in the femtosecond group (p=0.022 and <0.001). The overcorrection ratios were 48.8% in the conventional and 58.9% in the femtosecond group. (p<0.001). For patients with TIA over 0.75 D, SIA and correction index (TIA into SIA) was higher in femtosecond group (0.310 and 0.250, p<0.001 and <0.001, respectively). Absolute angle of error was 20.612±18.497 in the femtosecond group and higher than the conventional group (2.778, p=0.010). Conclusions: Femtosecond laser arcuate keratotomy in cataract surgery was effective in surgically induced astigmatism between 0.75 to 3.00 D of corneal astigmatism. However, the overcorrection in the lower astigmatism and angle of error in the higher astigmatism were due to the postoperative corneal astigmatism not decreasing as much as SIA. Overcoming these challenges will lead to better management of corneal astigmatism.